Applying Soft Systems Methodology in Enterprise Architecture Creation Workshops - Nakakawa, Agnes; Bommel, Patrick van; Proper, H.A. Erik (Enterprise modelling and information systems architectures, 2011)
Lack of effective involvement of stakeholders is one of the main drawbacks of enterprise architecture initiatives. Ongoing attempts to overcome this involve using Collaboration Engineering to develop a collaboration process that enterprise architects can execute to facilitate collaborative sessions with stakeholders during architecture creation. However, a field study evaluation of this process revealed that it offered inadequate support for stirring vigorous and rigorous discussions during activities that required organizing and assessing problem or solution aspects that resulted from brainstorming activities. Since Soft Systems Methodology (SSM) helps to structure rational thinking about messy situations, its techniques can be adapted to supplement the design of the collaboration process with support for triggering discussions and creating a shared understanding and vision among stakeholders. This paper therefore presents a script that shows how this can be done, and discusses its evaluation in a real case.
Keywords: Soft Systems Methodology; Architecture Creation Workshops; Enterprise